MOTIVATION AND PREPARATION FOR THE PROFESSIONAL DEVELOPMENT OF FUTURE TEACHERS - Kochkarova Elmira Rashidovna (Innovate Conferences, 2025)
In our republic, great attention is paid to the training of fully mature, competent, capable of independent thinking, strong-willed and enterprising personnel through the improvement of the education system. In the current period, the modernization of techniques and technologies in production, the rapid development of science and technology require specialists to independently and systematically deepen and expand their knowledge. An important factor in improving the educational process is inextricably linked to the high level of professional competence of teachers of technological education in the higher education system. Therefore, one of the urgent tasks is to create theoretical and practical foundations for the process of forming professional competence of teachers of technological education based on the effective use of the capabilities of modern educational technologies and the created educational methodological complexes. In this regard, the scientific substantiation of new approaches that ensure the level of professional competence required during the training of teachers of technological education in a higher educational institution is an urgent task.